Sustainable production of sago grown on tropical peat - Haruna, Ahmed Osumanu; Omar, Latifah; Petrus, Auldrey Chaddy; Ab Majid, Nik Muhammad (Universiti Putra Malaysia Press, 2012)
This book contains information of alternative ways in utilizing sago wastes (solid and liquid)and unwanted peat soil water. It discusses how products such as potassium-magnesium hydroxide,organic based fertilizers, humic acids, fulvic acids, humin and high quality compost are produced from sago fibres (hampas) after starch extraction. It further discusses how sago waste water, unwanted peat water and zeolite are used to amend urea to increase urea-N use efficiency in both waterlogged and non waterlogged conditions via reduction of ammonia volatilization from urea. This book will be of significant interest to those in the applied sciences,students, research scientists, farmers, environmentalists,fertilizer and related industries and so on.